Starting Time of Presbyopic Eyeglasses Wear and Lifestyle - Ayaki, Masahiko; Negishi, Kazuno; Kawashima, Motoko; Tsubota, Kazuo (Frontiers in Public Health, 2022)
Purpose Presbyopia is a serious burden in the aged population, however, the factors affecting its progression have not been fully determined. The aim of this study was to explore the association between the time of starting to wear presbyopic eyeglasses and lifestyle, in participants aged from 40 to 59 years. Methods We selected the sample to be representative of sex and age for the age group 40 to 59 years. Participants completed a web-based survey on presbyopia-related questions, symptomatic dry eye, sleep habits, Pittsburgh Sleep Quality Index, subjective happiness scale (SHS), and other lifestyle-related questions including marital status, income, screen time, sun exposure, family history of myopia, and the frequency of regular visits to medical services. Results We found 529 participants (26.5%) used near correction, with a mean age for first near correction of 47.8±4.8 years. An earlier commencement of near correction correlated with hyperopia (P = 0.013), late wake-up time (P = 0.010), a poor subjective sleep quality score (P = 0.019), and a low annual income score (P = 0.025), after adjusting for age and sex. Stratification by income demonstrated the low-income group exhibited more dry eye, later wake-up time, longer sleep latency, longer sleep duration, worse sleep efficacy, lower SHS score, and a higher prevalence of living alone compared with the high-income group. The usage of corrective devices did not differ between the two groups. Conclusions The current study suggests a healthy sleep habit may delay the need for near correction, in addition to myopia. Shift work and circadian rhythm disruption might exacerbate presbyopia progression.